Ingestão de nutrientes e anemia em crianças de creches municipais em Goiânia - BERALDO, Fernanda Carneiro (2008)
Introduction: The high prevalence of anemia, which is a serious public health problem, together with an early and in appropriate introduction of food for children, shows a close relationship between feeding practices and the presence of anemia. Objectives: To compare anemia among anemic and non-anemic children enrolled in municipal day nurseries of Goiânia, the socioeconomic and demographic characteristics, nutritional status, distribution of the consumption of macronutrients and the intake of micronutrients (calcium, iron and vitamin C), for Dietary Reference Intakes; evaluate and compare the ingestion of total iron, heme and non-heme iron and the bioavailable iron in the diets of anemic and non-anemic children from 12 to 24 months and compare the bioavailable iron according to algorithms developed by Monsen et al. and FAO / WHO. Methods: Observational study of cross-sectional analysis with children from 6 to 24 months in Goiânia-Goiás, in the years of 2005 and 2006. Investigations of socioeconomic, demographic and food (direct food weighing and 24 hour dietary recall) were applied for 2 days and the anthropometric evaluation and the dosage of hemoglobin were done. The diagnosis of anemia was determined by the level of hemoglobin less than 11 g / dL. Results: 89 children were studied. The prevalence of anemia was 53.9%. It was observed an statistically significant difference between anemic and non-anemic children as for per capita income. The proportion of macronutrients in the diets of the evaluated groups was appropriate and there was no difference statistically significant. Among the anemic children (n = 47), the prevalence of inadequacy was 12.8% for iron and 8.5% for vitamin C, whereas in the non-anemic ones (n = 41), the prevalence of inadequacy for iron and vitamin C was: 14.6% and 7.3%, respectively. The average intake of calcium was 50% above the recommendations in both groups. By the criterion of the World Health Organization, it was realized an anthropometric evaluation in three moments and the anemic had greater z-score according to the weight / length than non-anemic in the 2 and 3 moments (p = 0.015 p = 0.006) respectively . The average consumption of total iron, non-heme and bioavailable iron were low in the groups studied, showing no statistically significant difference. There was an intense positive correlation between the methodologies used to evaluate the iron bioavailable (r = 0.91 r = 0.84) for nonanemic and anemic children, respectively. Conclusion: There was a statistically difference between per capita income and anemia. It was observed a greater z-score for the index weight / length in the anemic children. There was no statistically difference between the two groups in relation to the consumption of calcium, iron and vitamin C, however there was a significant prevalence of inadequacy of iron and vitamin C, besides a high intake of calcium in the diet. There was a low total consumption of iron, heme and non-heme and bioavailable iron that reinforces the importance of the knowledge of food consumption of children, as well as the adoption of measures that ensure the supply of food sources of iron and food promoters of bioavailability of this micronutrient.